(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The aim of this research is to determine the effectiveness of using the Quick Response Code Indonesian Standard (QRIS) as a non-cash payment method on the Trans Mamminasata Bus in Makassar City. This research uses qualitative methods, with a qualitative descriptive research type where data collection techniques are carried out through observation, interviews and documentation. The research results show that (a) the accuracy of the program targets shows that the use of QRIS is still less effective in targeting the general public and all users of Teman Bus services. (b) socialization of the program, showing that it is almost effective because it is not only carried out directly. (c) program objectives, indicating that payments via the Indonesian Standard Quick Response Code (QRIS) aim to make it easier for passengers. (d) program monitoring, showing that the monitoring carried out is almost effective but there are still many people who do not know whether there is monitoring carried out by parties related to Friends of the Bus.